Nonsteroidal Anti-inflammatory Drugs Are Not Associated With Increased Bleeding in Blunt Solid Organ Injury. Issue 5 (September 2022) - Hill, Joshua H.; Kuhlman, Jamie; LaRiccia, Aimee; Ngo, Anna; Hyland, Sara Jordan; Spalding, Marshall C.
Abstract : BACKGROUND: Nonsteroidal anti-inflammatory drugs are an effective nonopiate option for pain control. However, the antiplatelet aggregation of cyclooxygenase-1 (COX-1) inhibitors presents a concern in that they may exacerbate bleeding in patients with solid organ injuries. OBJECTIVE: The aim of the study is to evaluate the impact of nonsteroidal anti-inflammatory drugs on blunt solid organ injury. We hypothesized that nonsteroidal anti-inflammatory drugs would not contribute to intra-abdominal bleed progression. METHODS: This is a retrospective cohort study of blunt solid organ injury evaluated from June 1, 2015, to June 30, 2019, at an urban midwestern Level I trauma center. Patients receiving and those not receiving nonsterioidal anti-inflammatory drugs were compared on intra-abdominal bleeding progression as assessed by surgical intervention, angioembolization, and blood transfusions. RESULTS: We analyzed 706 patients, of whom 206 were given nonsteroidal anti-inflammatory drugs during their hospital course. Compared with those who were not given nonsteroidal anti-inflammatory drugs, patients given nonsteroidal anti-inflammatory drugs were less likely to have an operation (odds ratio, OR 0.46, 95% confidence interval, CI [0.25, 0.85], p = .012) and were less likely to have an embolization (OR 0.27, 95% CI [0.11, 0.70], p = .004). There was no difference in the need for packed red blood cell transfusion between the nonsteroidal anti-inflammatory drug and non- nonsteroidal anti-inflammatory drug groups (95% CI [0.91, 1.99], p = .13). CONCLUSION: Patients given nonsteroidal anti-inflammatory drugs had a decreased likelihood of receiving an organ-specific procedure or needing a blood transfusion and had no difference in mortality. Our findings indicate that nonsteroidal anti-inflammatory drugs in patients with blunt solid organ injuries were not associated with an increased risk of adverse events related to intra-abdominal bleeding.